Sympathy for the devil: state engagement with criminal organisations in furtherance of public policy. Issue 3 (3rd July 2019) - Grabosky, Peter
ABSTRACT: Governments have long relied on non-state actors to assist in the implementation of public policy. Legitimate elements of civil society have become familiar instruments of governance. States have also engaged criminal actors to this end. This article will note examples of state collaboration with criminal interests, from pirates turned privateers during the 17th and 18th centuries, to the patriotic hackers of today. It will discuss the strategic considerations giving rise to such engagements, the pitfalls that may beset them, and the ethical considerations that might inform the decision by a state to enlist the services of illicit organisations.